2014
DOI: 10.5114/pm.2014.42714
|View full text |Cite
|
Sign up to set email alerts
|

The role of angiogenic factors in endometrial cancer

Abstract: Endometrial cancer is the most common malignancy within the female reproductive system (37.7%). The incidence increases with age. Frequently this type of cancer is diagnosed in peri- and post-menopausal women. 60-70% of cancers occur in women over 60 years of age, and less than 5% in women below 40 years of age.Angiogenesis is a process of formation of new microvessels from existing capillaries. There are four different mechanisms of new vessel growth: sprouting, intussusception, vessel elongation and incorpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…Statistically significant plasma overexpression and high gene expression of VEGF-A, VEGF-B and VEGFR-1 have been detected in patients suffering from many types of tumors, also breast cancer (Takahashi, 2011;De Falco, 2012;Thielemann et al, 2013;Lawicki et al, 2013;Żyła et al, 2014;Bry et al, 2014;Ławicki et al, 2016). We have demonstrated statistically significantly higher plasma concentrations of tested parameters in BC patients compared to control groups.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Statistically significant plasma overexpression and high gene expression of VEGF-A, VEGF-B and VEGFR-1 have been detected in patients suffering from many types of tumors, also breast cancer (Takahashi, 2011;De Falco, 2012;Thielemann et al, 2013;Lawicki et al, 2013;Żyła et al, 2014;Bry et al, 2014;Ławicki et al, 2016). We have demonstrated statistically significantly higher plasma concentrations of tested parameters in BC patients compared to control groups.…”
Section: Discussionsupporting
confidence: 55%
“…VEGF-A was discovered in 1989. Its gene consists of 8 exons and plays an important role in the process of blood vessels forming (Leung et al, 1989;Żyła et al, 2014). It is synthesized by various cell types, including mast cells, smooth muscle cells in vessels, macrophages, fibroblasts, endothelial cells, monocytes, keratinocytes, eosinophils, T lymphocytes and cancer cells (Weryńska et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…VEGF plays a crucial role in the initiation of physiological and pathological angiogenesis. Elevated levels of VEGF have been shown in patients with endometrial cancer [22]. Studies have shown a relationship between the blood level of VEGF and the clinical stage of cancer [23].…”
Section: Serum Biomarkersmentioning
confidence: 99%
“…The world records show approximately 189,000 new cases of endometrial cancer and 45,000 deaths a year [ 3 ]. The highest incidence rates occur in North American, European, and Australian countries, while the lowest are in countries in Asia and Africa [ 4 ].…”
Section: Introductionmentioning
confidence: 99%